Kalimat Tanya pada Percakapan Tokoh Utama dalam Noveltoon Kulepas Kau Dengan Bismillah Karya D'wie: Interrogative Sentences in the Main Character's Conversation of Noveltoon Kulepas Kau Dengan Bismillah by D'wie - Hendrawati, Maulina; Ngatmini, Ngatmini; Kurniawan, Latif Anshori (Universitas Tidar, 2025)
The aim of this research is to describe the types of interrogative sentences in the NovelToon Kulepas Kau dengan Bismillah by D'wie. The research method used in this research is descriptive qualitative by describing the use of interrogative sentences in the conversation of the main character in the NovelToon Kulepas Kau with Bismillah. The results of this research include four types of question sentences, there are 196 ordinary question sentences, 17 rhetorical question sentences, 58 disguised question sentences, and 89 clarifying questions. Of the four types of question sentences, 361 quotations were found, the most dominant type of question sentence used in NovelToon Kulepas Kau dengan Bismillah by D'wie was a regular question sentence which appeared 196 times, while rhetorical question sentences with 17 quotations were the most common type of question sentence. appeared a little. The reason why there are more ordinary interrogative sentences in D'wie's NovelToon Kulepas Kau dengan Bismillah is because ordinary interrogative sentences are often used to obtain information directly, often appear in everyday communication, and have a simple structure. Meanwhile, rhetorical question sentences are used less often because they aim to express feelings without requiring an answer.